Legal Consequences for Deed that is Not Signed Before a Notary - Putu Ayu Sriasih Wesna; I Gusti Putu Dena Dharma Putra (Kertha Wicaksana, 2023)
Notary Deed Signing is not in the notary’s office, even though the act is at risk of violating the rules of the notary position law and notary code of ethics, but it is still carried out by certain notaries. This type of research is normative legal research. With normative juridical methods. Legal materials consist of primary, secondary and tertiary legal materials. The analysis method uses the description technique, construction technique, and systematic technique. The validity of a deed not signed before a notary, the deed is only valid as an agreement, where a valid agreement is an agreement that has fulfilled the legal requirements of an agreement such as an agreement, the ability of the parties, the object of the agreement, and the agreement made is not contrary to the law applicable. The validity of the deed is invalid, because in signing the deed that was not performed before a notary, the authentic deed did not fulfill the formal requirements to become an authentic deed as regulated in Article 16 paragraph (1) letter m of Law Number 2 of 2014 concerning Amendment to the Law Number 30 of 2004 concerning Notary Position. Where in this provision that the Notary must be physically present and sign the deed in front of the parties, witnesses, and the Notary himself. Notary Deed that is not signed by the registrar before a notary public and signed outside the Notary’s office, even though on the grounds that one of the registrants cannot be present at the signing of the deed by the tappers, and witnessed by witnesses and Notaries, resulting in the degradation of the authentic deed becomes the only deed has a proof of deed under the deed. In Act Number 2 of 2014 concerning amendments to Act Number 30 of 2004 concerning Notary Position, no regulation is found concerning sanctions against Notaries that are significant for violations of Article 16 paragraph (1) letter m of Act Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning Notary Position.